Chemical Composition and Insecticidal Activity of Origanum syriacum L. Essential Oil Against Sitophilus oryzae and Rhyzopertha dominica - Tunay Karan; Seyda Simsek; Ilyas Yildiz; Ramazan Erenler (International Journal of Secondary Metabolite)
Origanum genus belonging to the Lamiaceae family is aromatic and medicinal plant. It has been used in many countries for medicinal and pharmaceutical purpose. Aerial part of the Origanum syriacum L. was dried at shade. The essential oil was generated by steam distillation and compounds were identified by GC-MS analysis. γ-terpinene (26.7%), thymol (26.6%) and carvacrol (22.9%) was detected as the mail constituents. The essential oil was tested for insecticidal activity against adult of Sitophilus oryzae (L.) (Coleoptera: Curculionidae) and Rhyzopertha dominica (F.) (Coleoptera: Bostrychidae) using fumigation method. Essential oil revealed the excellent fumigant effect on R. dominica adults with a median lethal concentration (LC50) value of 0.124 µl/insect and 0.107 µl/insect for 48 h and 72 h respectively. LC50 values of S. oryzae were found as 0.173 µl/insect and 0.135 µl/insect for 48 h and 72 h respectively. As a result, essential oil of O. syriacum has a potency to be a natural insecticide.